Preserving CTA’s intellectual property assets - Khadar, Ibrahim (Technical Centre for Agricultural and Rural Cooperation, 2020)
In the run-up to the closure of CTA at the end of 2020, the Centre implemented a rigorous process to take stock of its intellectual legacy assets and plan for their responsible transfer, retention or disposal, in close consultation with EU and ACP stakeholders.